PEER TUTORING TO IMPROVE ENGLISH LEARNING OUTCOMES IN KELAS VIII-1 IN SMP NEGERI 1 PADANGSIDIMPUAN - Masdariana Dalimunthe (Institut Pendidikan Tapanuli Selatan, 2021)
This qualitative study was conducted in Kelas VIII-1 in SMP Negeri 1 Padangsidimpuan. This is an Online Classroom Action Research did in two cycles with 25 students as participants dealing with how the implementation of Peer Tutoring can improve students’ learning outcomes in English learning. Data were collected through observation and document analysis and the finding then reviewed as well as analyzedqualitatively based on the theories proposed in thisstudy. This research then proves the following points. The implementation of Peer Tutoring online is significant to improve students' learning outcomes in KelasVIII-1 in SMP Negeri 1 Padangsidimpuan. Teachers should be wise in choosing students who will be made as tutors because in tutoring students not only need to have adequate cognitive skills but also need tohave leadership capability. However, before implementing the Peer Tutoring the teacher should make careful preparations in order to be able to perform effective and optimallearning process. The implementation of this teaching model requires hard work for teacher because maximal effort need to be conducted in performing online learning. Thus, further research is still needed in broaden scale for better achievement.